A Pragmatic Analysis of Impoliteness Strategies in Trevor Noah’s Stand-Up Comedy: I Wish You Would - Ramli, Fadhel (Paradigma Lingua, 2025)
This study investigates the types and functions of impoliteness strategies in Trevor Noah’s Netflix stand-up comedy special I Wish You Would. While impoliteness has often been studied in conflict-driven interactions, its role in comedic performance remains less explored. Using Culpeper’s (1996) typology of impoliteness strategies and his (2011) functional framework, the research applies a qualitative descriptive approach to 30 purposively selected utterances from the show. The analysis identified four types of impoliteness strategies: sarcasm (10 utterances, 33%), negative impoliteness (10 utterances, 33%), positive impoliteness (6 utterances, 20%), and bald-on-record impoliteness (4 utterances, 14%). Withhold impoliteness did not appear in the data. Regarding their functions, the majority of instances served an entertaining purpose (23 utterances, 70%), followed by coercive (3 utterances, 10%) and affective (4 utterances, 13%). These findings demonstrate that in stand-up comedy, impoliteness functions less as an offensive act and more as a rhetorical device for humor, social critique, and audience engagement. In Noah’s performance, impoliteness enables him to address sensitive issues in ways that entertain while softening the potential harshness of critique.